In vitro evaluation of essential oils for potential antibacterial effects against Xylella fastidiosa. Issue 11 (30th October 2018) - Santiago, Mariana Brentini; Moraes, Thaís da Silva; Massuco, Jaqueline Estétele; Silva, Larissa Oliveira; Lucarini, Rodrigo; da Silva, Danielle Fernandes; Vieira, Tatiana Manzini; Crotti, Antônio Eduardo Miller; Martins, Carlos Henrique Gomes
Abstract: The main pathogen underlying citrus variegated chlorosis (CVC), a citrus fruit disease, is Xylella fastidiosa, a Gram‐negative s‐shaped bacterium that blocks water and nutrient circulation. Discovering new pesticides to combat CVC have become a challenge. Research into essential oils (EOs) is crucial because these substances can be potentially useful in pest control. This study aims to determine minimum inhibitory concentrations (MIC), to investigate biofilm inhibition capacities through MBIC50 analysis, and to evaluate synergistic effects with streptomycin of 17 EOs against X. fastidiosa . This study also analyses the chemical profiles of the EOs that provided the best antibacterial activity results. The MIC values of the EOs ranged from 125 to 1, 000 µg/ml. Analysis of the MICB50 values of the sandalwood and patchouli EOs revealed biofilm inhibitory activity. No synergistic effects were evident for streptomycin combined with the sandalwood or patchouli EOs: ΣFIC was 1.25 and 1.5, respectively, which denoted indifference. We detected α‐gurjunene (27.6%), patchouli alcohol (21.6%), α‐bulsene (17.3%) and α‐patchoulene (6.3%) as the major patchouli EO constituents. On the basis of our results, the sandalwood and patchouli EOs present antibacterial action and are promising natural sources for the development of new pesticides against X. fastidiosa .